The pattern of economic growth in Indonesia in comparison with Malaysia and Thailand - Niswatil Mouna (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2021)
The pattern of economic growth in Indonesia between 1995 and 2005 was analyzed to determine structural changes that occurred in Indonesia. A hypothetical analysis of Deviation from Proportional Growth was used in this study to better understand the structural change of a country by assuming a virtual economic structure. The author analyzed the Indonesian National Input-Output Table of 1995, 2000, and 2005 extracted from the Asian International Input-Output Table. A comparative study was also conducted for Malaysia and Thailand during the same period. The results revealed a shift away from the agricultural sector towards non-agricultural sectors in Indonesia, Malaysia, and Thailand between 1995 and 2005, confirming the existence of industrialization in these countries. Although the countries had a similar pattern of growth which is contributed mainly by the expansion of export from 1995–2000, the pattern of growth among the three countries was divergent from 2000–2005.